2013
DOI: 10.1371/journal.pone.0059570
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants in the Folate Pathway and the Risk of Neural Tube Defects: A Meta-Analysis of the Published Literature

Abstract: BackgroundNeural Tube Defects (NTDs) are among the most prevalent and most severe congenital malformations worldwide. Polymorphisms in key genes involving the folate pathway have been reported to be associated with the risk of NTDs. However, the results from these published studies are conflicting. We surveyed the literature (1996–2011) and performed a comprehensive meta-analysis to provide empirical evidence on the association.Methods and FindingsWe investigated the effects of 5 genetic variants from 47 study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
82
2
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 45 publications
0
82
2
4
Order By: Relevance
“…34 Several meta-analysis studies illustrate the utility of the technique in identifying genes of small effects like MTHFR with phenotypes like -NTD, 35 Down syndrome, 36 Cardiovascular disease, 37 Migraine, 38 Schizophrenia, 39 bipolar disorder, 40 and depression. 41 The present meta-analysis (including 1019 case mothers and 16494 controls) was performed to assess the relationship between MTHFR A1298C polymorphism and NSCL/P with ten published case control studies, but no significant association was found in the total population.…”
Section: Discussionmentioning
confidence: 99%
“…34 Several meta-analysis studies illustrate the utility of the technique in identifying genes of small effects like MTHFR with phenotypes like -NTD, 35 Down syndrome, 36 Cardiovascular disease, 37 Migraine, 38 Schizophrenia, 39 bipolar disorder, 40 and depression. 41 The present meta-analysis (including 1019 case mothers and 16494 controls) was performed to assess the relationship between MTHFR A1298C polymorphism and NSCL/P with ten published case control studies, but no significant association was found in the total population.…”
Section: Discussionmentioning
confidence: 99%
“…The association of MTHFR polymorphisms with the increased risk of OFC supports the protective effect of maternal use of multivitamins containing folic acid with respect to the occurrence of orofacial clefts (Bailey et al, 2005). Several meta-analysis studies illustrate the utility of the technique in identifying genes of small effects like MTHFR with phenotypes like-NTD (Zhang et al, 2013); down syndrome (Zintzaras, 2007;; cardiovascular disease (Xuan et al, 2011), stroke (Yadav et al, 2013); migraine (Shurks et al, 2010), Alzheimer's (Zhang et al, 2010), bipolar disorder (Rai, 2011), and depression (Zintzaras, 2006;. Author identified one meta-analysis (Verkleij-Hagoort et al, 2007) published in 2007 concerning similar topic during the literature search.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that MTHFR C677T SNP was associated with a significant risk of neural tube defects in the developing foetus, as well as repetitive miscarriages and cardiovascular disorders in adults [1,[21][22][23]. However, despite proven correlation between the above-mentioned risk of cardiovascular disorders and 677T allele prevalence, the contribution of this MTHFR variant to the increased risk of vein thrombosis remains equivocal.…”
Section: C677tmentioning
confidence: 99%